Emergencias psiquiátricas - Valdivia Ponce , Oscar (1973)
It is our the intention to give to oyr Medical Community some rules for resolving therapeutically the psychiatric emergencies. With this ention we try to define the emergency, its characteristies and the main elements. We give some rules for its study, the diagnostic and the therapeutic management in the individual and collective emergencies.